PRODUKSI PROGRAM TELEVISI: Sebuah proses kreatif menuju industri kreatif - DA, NRA. Candra (Seni Media Rekam ISI Surakarta, 2009)
A producer or program maker of a audio visual have to posses the sense of creativity in searching the material of program production. This can be appeared from the experience, education and critical attitude. The producer who does not have a clear vision will produce an audio visual product that is limit quality and duplicate another programs that have been ever exist. Meanwhile a television channel needs a innovative strategy to propose the program.Â Keyword : television program, creative process, creative industry